HUBUNGAN ANTARA WAKTU TUNGGU PELAYANAN RESEP TERHADAP TINGKAT KEPUASAN PASIEN DI PUSKESMAS KELAYAN DALAM - Amaliyah Wahyuni; Mochammad Maulidie Alfiannor Saputera; Novia Ariani; Anna Khumaira Sari; Mawaddah Mawaddah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Prescription service is one of the pharmaceutical at public health center. One of the minimum standards of pharmacy service at public health center is the waiting time. The prescription waiting time is the patient's waiting time for prescribing medicines that start from prescription received at TTK until the patient is finished receiving the medicines. A great service in waiting time can affect patient satisfaction, so the public health center should be able to control the service time to achieve patient satisfaction.The purpose of this research is to know the illustration of prescription waiting time and the levels of patient satisfaction, also correlation between prescription waiting time with patient satisfaction at public health center Kelayan Dalam.The type of research is descriptive analytic. The Sample is done by non probability sampling using purposive sampling method and statistical data analysis technique is done by using SPSS 17.0 that is Chis Square test. The research was conducted from May to June in 2018, with a total of 178 respondents. Data collection was done with observation sheet for prescription waiting time and questionnaire about patient satisfaction which has been done with valid and reliable test.The results showed that of 178 respondents in the illustration of the waiting time for non-concoction prescription is about 4,25 minutes and for the concoction prescription is about 7,71 minutes, the results are in compliance with the standards set by the head of the public health center, the results of research in satisfaction level with the percentage of 74, 85% are in the satisfied category. And statistic result show sig value 0,001 <0,05 that there is a significant correlation between prescription waiting time and patient satisfaction level so that if the prescription waiting time can be faster then the feeling of satisfaction in patient can be higher too.